2022
DOI: 10.1101/2022.01.05.22268800
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between vaccination status and reported incidence of post-acute COVID-19 symptoms in Israel: a cross-sectional study of patients tested between March 2020 and November 2021

Abstract: Background: Long COVID is a post-severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection syndrome characterised by not recovering for several weeks or months following the acute episode. The effectiveness of COVID-19 vaccines against long-term symptoms of COVID19 is not well understood. We determined whether vaccination was associated with reporting long-term symptoms post-SARS-CoV-2 infection by comparing, among individuals previously infected with SARS-CoV-2, those who were vaccinated to those… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
1
4

Year Published

2022
2022
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 23 publications
6
103
1
4
Order By: Relevance
“…Furthermore, the risk of developing CNS diseases after infection with SARS-CoV-2 might change after vaccination or prior to SARS-CoV-2 infection. It has already been shown that vaccination partly protects against the development of long COVID [99]. Other variables that might influence the development of CNS disease include, for example, the infection dose and primary replication site of the virus [73].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the risk of developing CNS diseases after infection with SARS-CoV-2 might change after vaccination or prior to SARS-CoV-2 infection. It has already been shown that vaccination partly protects against the development of long COVID [99]. Other variables that might influence the development of CNS disease include, for example, the infection dose and primary replication site of the virus [73].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding Covid-19 vaccination as a possible preventive intervention, findings from a recent (published since our search) observational study indicate that receiving Covid-19 vaccine after getting infected might offer some protection against long Covid-19 outcomes (74). Other studies we identified from our search or have identified thereafter did not meet inclusion criteria (e.g., vaccination before infection (75, 76), indeterminate timing of vaccination (77), entire sample had post Covid-19 condition (78, 79)). Variations in definition of post Covid-19 outcomes and timing of assessment make it difficult to draw conclusions or compare the findings of our review with other studies.…”
Section: Discussionmentioning
confidence: 99%
“…A small-scale study found a modest overall improvement in the symptoms of 44 patients with long COVID vaccinated against COVID-19, compared with 22 unvaccinated patients 9 . Finally, a recent cross sectional study found that vaccinated patients reported, on average, 50% less post-acute COVID-19 symptoms than unvaccinated patients 10 . Unfortunately, in this study, the vaccination status at the time of infection was unknown and therefore some individuals were infected prior to vaccination while others were vaccinated after.…”
Section: Introductionmentioning
confidence: 94%